The ‘Hot Cross Bun’ Sign Is Not Always Multiple System Atrophy: Etiologies of 11 Cases - Christopher Way; David Pettersson; Amie Hiller (Journal of Movement Disorders, 2019)
Objective To clarify the specificity of the ‘hot cross bun’ sign (HCBS) for multiple system atrophy (MSA) in adult cerebellar ataxia or parkinsonism. Methods The radiologic information systems at an academic center and affiliated veterans’ hospital were queried using the keywords ‘hot cross bun,’ ‘pontocerebellar,’ ‘cruciate,’ ‘cruciform,’ ‘MSA,’ ‘multiple system atrophy,’ and ‘multisystem atrophy.’ Scans were reviewed by a neurologist and neuroradiologist to identify the HCBS. Subjects with the HCBS were reviewed by 2 neurologists to identify the most likely etiology of the patient’s neurologic symptoms. Results Eleven cases were identified. Etiologies included MSA (4 probable, 2 possible), hereditary cerebellar ataxia (3/11), probable dementia with Lewy bodies (1/11), and uncertain despite autopsy (1/11). Conclusion MSA was the most common etiology. However, 5 of the 11 patients did not have MSA. The most common alternate etiology was an undefined hereditary cerebellar ataxia (3/11).